Hit and run oncogeneses in head and neck cancers requires greater investigation. Issue 1 (10th November 2022) - Goon, Peter; Sudhoff, Holger; Goerner, Martin
Abstract: Head and neck cancers are unique in so far that two major oncogenic viruses, Epstein Barr virus (EBV) and Human papillomavirus (HPV) infect adjacent anatomy and cause nasopharyngeal and oropharyngeal cancers, respectively. Dominant recognized carcinogens are alcohol and tobacco but some head and neck cancers have been found to have mixed carcinogens (including betel leaf, areca nuts, slaked lime, viruses, etc.) involved in their oncogenesis and conversely, groups of patients with unknown or less dominant carcinogens involved in their development. These cancers may have had viral involvement in the past but then lost most of their viral nucleic acids (be they DNA and/or RNA) below a detection threshold, thus rendering them virus‐negative. Some of these virus‐negative tumors appear to have mutagenic signatures associated with virus‐positive cancers, for example, from the APOBEC defense mechanism which is known to mutate viral nucleic acids as well as cause collateral damage to host DNA, with subsequent development of strongly viral prejudiced mutational signatures. These mechanisms are likely to be less efficient at oncogenesis than traditional EBV and HPV oncogenes directly driving mutagenesis, thus accounting for the smaller frequencies of these cancers found. More profound investigations of these unusual tumors are warranted to dissect out these mechanistic pathways.